A mixed treatment comparison meta-analysis of metaphylaxis treatments for bovine respiratory disease in beef cattle - Abell, Kaitlynn M.; Theurer, Miles E.; Larson, Robert L.; White, Bradley J.; Apley, Michael D. (My University, 2017)
The objective of this project was to evaluate the effects of antimicrobials approved for parenteral metaphylactic use in feeder and stocker calves on morbidity and mortality for bovine respiratory disease with the use of a mixed treatment comparison meta-analysis. An initial literature review was conducted in April 2016 through Pubmed, Agricola, and CAB (Commonwealth Agricultural Bureau) for randomized controlled trials for metaphylaxis antimicrobial administered parentally to incoming feedlot or stocker calves within 48 h of arrival. The final list of publications included 29 studies, with a total of 37 trials. There were 8 different metaphylactic antimicrobials. Final event outcomes were categorized into bovine respiratory disease (BRD) morbidity cumulative incidence d 1 to <= 60 of the feeding period, BRD morbidity cumulative incidence d 1 to closeout of the feeding period, BRD mortality cumulative incidence d 1 to closeout of the feeding period, and BRD retreatment cumulative incidence morbidity d 1 to closeout of the feeding period. Network meta-analysis combined direct and indirect evidence for all the event outcomes to determine mean odds ratio (OR) with 95% credibility intervals (CrIs) for all metaphylactic antimicrobial comparisons. The "upper tier" treatment arms for morbidity d 1 to <= 60 included tulathromycin, gamithromycin, and tilmicosin. For BRD mortality cumulative incidence d 1 to closeout and BRD retreatment morbidity d 1 to closeout, classifying the treatment arms into tiers was not possible due to overlapping 95% CrIs. The results of this project accurately identified differences between metaphylactic antimicrobials, and metaphylactic antimicrobial options appear to offer different outcomes on BRD morbidity and mortality odds in feedlot cattle.
Citation: Abell, K. M., Theurer, M. E., Larson, R. L., White, B. J., & Apley, M. (2017). A mixed treatment comparison meta-analysis of metaphylaxis treatments for bovine respiratory disease in beef cattle. Journal of Animal Science, 95(2), 626-635. doi:10.2527/jas2016.1062
Keywords: Antimicrobial; Bovine Respiratory Disease; Meta-Analysis; Metaphylaxis; Mixed Treatment Comparison; Feedlot Calves